2002
DOI: 10.1016/s0167-8191(02)00191-6
|View full text |Cite
|
Sign up to set email alerts
|

Parallel components for PDEs and optimization: some issues and experiences

Abstract: High-performance simulations in computational science often involve the combined software contributions of multidisciplinary teams of scientists, engineers, mathematicians, and computer scientists. One goal of component-based software engineering in large-scale scientific simulations is to help manage such complexity by enabling better interoperability among codes developed by different groups. This paper discusses recent work on building component interfaces and implementations in parallel numerical toolkits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Experiments have shown that the overheads for calls between directly connected CCA components are small and quite manageable in the context of scientific computing Norris et al 2002;. Calls using simple data types (those requiring no translation by Babel) cost the equivalent of a C++ virtual function call, exactly what is expected for the direct connection implementation described above.…”
Section: Fine-grained Component Interactionsmentioning
confidence: 84%
See 1 more Smart Citation
“…Experiments have shown that the overheads for calls between directly connected CCA components are small and quite manageable in the context of scientific computing Norris et al 2002;. Calls using simple data types (those requiring no translation by Babel) cost the equivalent of a C++ virtual function call, exactly what is expected for the direct connection implementation described above.…”
Section: Fine-grained Component Interactionsmentioning
confidence: 84%
“…• Norris and coworkers (Norris et al 2002) have compared a CCA component implementation and a non-component library implementation of a nonlinear unconstrained minimization problem solved using an inexact Newton method with a line search (Norris et al 2002). Each iteration of the Newton method required function, gradient, and Hessian evaluations, as well as an approximate solution of a linear system of equations.…”
Section: Parallel Componentsmentioning
confidence: 99%
“…XCAT3 [12] is another CCA implementation that supports components distributed over different address spaces and accessible as collections of Grid services compliant to OGSI (Open Grid Services Infrastructure). In [16], CCA/Ccaffeine is used to componentise simulation software for partial differential equations. Components are produced by creating thin wrappers over existing numerical libraries.…”
Section: Related Workmentioning
confidence: 99%
“…The amount of extra code needed to acclimate a software module to the CCA environment can be as little as one extra (typically short) method, and several additional calls that manage ports provisioning and use. Experience has shown that componentization of existing software in the CCA environment is straightforward when starting from well-organized code [10].…”
Section: Computer Science: the Common Component Architecturementioning
confidence: 99%